To evaluate a variable expression involving integers, replace the variables in the expression by the given values of the variables and simplify PEMDAS.
PEMDAS is the rule that can be used to simplify or evaluate complicated numerical expressions with more than one binary operation.
P ----> Parentheses
E ----> Exponent
M ----> Multiply
D ----> Divide
A ----> Add
S ----> Subtract
Important Notes :
1. In a particular simplification, if you have both multiplication and division, do the operations one by one in the order from left to right.
2. Division does not always come before multiplication. We have to do one by one in the order from left to right.
Example 1 :
Evaluate the expression for x = 2.
5 + x
Solution :
= 5 + x
Substitute x = 2.
= 5 + 2
= 7
Example 2 :
Evaluate the expression for x = -1.
-x + 5
Solution :
Substitute x = -1.
= -x + 5
= -(-1) + 5
= 1 + 5
= 6
Example 3 :
Evaluate the expression for p = 3.
p - 6
Solution :
= p - 6
Substitute p = 3.
= 3 - 6
= -3
Example 4 :
Evaluate the expression for r = -2.
-r + 5
Solution :
= -r + 5
Substitute r = -2.
= -(-2) + 5
= 2 + 5
= 7
Example 5 :
Evaluate the expression for m = 0.
m - 5
Solution :
= m - 5
Substitute m = 0.
= 0 - 5
= -5
Example 6 :
Evaluate the expression for t = -4.
5t - 3
Solution :
= 5t - 3
Substitute t = -4.
= 5(-4) - 3
= -20 - 3
= -23
Example 7 :
Evaluate the expression for x = 5 and y = 6.
x + y - 9
Solution :
= x + y - 9
Substitute x = 5 and y = 6.
= 5(-4) - 3
= -20 - 3
= -23
Example 8 :
Evaluate the expression for x = 2 and y = -3.
3x + 2y
Solution :
= 3x + 2y
Substitute x = 2 and y = -3.
= 3(2) + 2(-3)
= 6 - 6
= 0
Example 9 :
Evaluate the expression for m = -1 and n = -2.
-2m + 3n + 5
Solution :
= -2m + 3n + 5
Substitute m = -1 and n = -2.
= -2(-1) + 3(-2) + 5
= 2 - 5 + 5
= 2
Example 10 :
Evaluate the expression for p = 5 and q = 7.
(5/p) + (7/q)
Solution :
= (5/p) + (7/q)
Substitute p = 5 and q = 7.
= (5/5) + (7/7)
= 1 + 1
= 2
Example 11 :
Evaluate the expression for x = 5, y = 8 and z = 6.
(y2 + z) ÷ x
Solution :
= (y2 + x) ÷ x
Substitute x = 5, y = 8 and z = 6.
= (82 + 6) ÷ 5
= (64 + 6) ÷ 5
= 70 ÷ 5
= 14
Example 12 :
Evaluate the expression for p = 6, q = 5 and r = 4.
(pq - 28)2 ÷ r
Solution :
(pq - 28)2 ÷ r
Substitute p = 6, q = 5 and r = 4.
= [(6)(5) - 28]2 ÷ 4
= (30 - 28)2 ÷ 4
= 22 ÷ 4
= 4 ÷ 4
= 1
Kindly mail your feedback to v4formath@gmail.com
We always appreciate your feedback.
©All rights reserved. onlinemath4all.com
Feb 05, 25 12:22 PM
Feb 05, 25 12:15 PM
Feb 04, 25 08:16 AM